Telling the untellable: dialectic of silence in Jewish-American and Arab- American Holocaust discourse - Al-Aghberi, Munir Ahmed (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
The present paper attempts to cast light on an important aspect of Holocaust literature. Basically, it is an investigation into two ideological responses to the Shoah that, though characterised by the dominant element of silence, both are marked by essential discrepancies. One sort of responses finds in silence a trope for the incommunicability of the trauma; the counter response professes silence as a fragile way of protest and resistance. This paradoxical dialectic of silence is traced in both Jewish-American and Arab-American literary discourses as emblematic contexts of the discrepancy in the Holocaust representation. Silence, as examined herein, is found to typify a meta-narrative arising from the tension between sacred memory and subversive amnesia. It effectively re-enacts the conflicting histories of loss and trauma where the deliberate absence of voice is believed to convey what words mostly fall short of and thus it could enhance one’s status of victimhood.